2006
DOI: 10.1248/bpb.29.623
|View full text |Cite
|
Sign up to set email alerts
|

Berberry Extract Reduces Neuronal Damage and N-Methyl-D-aspartate Receptor 1 Immunoreactivity in the Gerbil Hippocampus after Transient Forebrain Ischemia

Abstract: Transient forebrain ischemia, produced by prolonged deprivation of blood flow to the brain, results in the insidious delayed degeneration of specific vulnerable neurons within the hippocampus.1,2) Among hippocampal neurons, pyramidal cells of the hippocampal CA1 region are most vulnerable to cerebral ischemia. 1,2) Death of the CA1 pyramidal cells following cerebral ischemia causes a variety of neurological dysfunction such as depression and memory deficits. 3,4) In traditional Eastern medicine, the extracts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 35 publications
(30 reference statements)
4
38
0
1
Order By: Relevance
“…It has been reported that berberine attenuated neuronal damage in ischemia/reperfusion model (Yoo et al, 2006) and enhances neuronal cell survival and differentiation in rat's hippocampus (Lim et al, 2008). In addition, CF extract have been previously reported to exhibit the neuroprotective effect via its antioxidant activity leading to the decreased oxidative stress and finally decreased neurodegeneration in neonatal animal model (Lee et al, 2010).…”
Section: Ajptmentioning
confidence: 98%
“…It has been reported that berberine attenuated neuronal damage in ischemia/reperfusion model (Yoo et al, 2006) and enhances neuronal cell survival and differentiation in rat's hippocampus (Lim et al, 2008). In addition, CF extract have been previously reported to exhibit the neuroprotective effect via its antioxidant activity leading to the decreased oxidative stress and finally decreased neurodegeneration in neonatal animal model (Lee et al, 2010).…”
Section: Ajptmentioning
confidence: 98%
“…It has been demonstrated that BR has multiple pharmacological effects such as antimicrobial [10], anti-inflammatory [10] and anticancer activity [11]. In addition, BR is a promising drug for treating Alzheimer’s disease [12], forebrain ischemia [13], anxiety [14] and depression [15]. Most interesting for our research, BR has various beneficial effects on the cardiovascular system, including antihyperglycemic activity [16], lowering blood pressure [17] and antihyperlipidemia [18].…”
Section: Introductionmentioning
confidence: 99%
“…Berberine has varied pharmacological effects including anti-diarrheic [11] , antimicrobial [12] , and anti-inflammatory [13] ; it also exhibits protective effects against ischemic damage after ischemia/reperfusion [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%